Strategi Mahasiswa UINSU Dalam Menanggapi Penyebaran Berita Hoaks Pada Media Sosial Tiktok - Nursistani Siallagan; M Bintang Chadavi M; Nazwa Ramadhani; Radhita Aulia Ramadhana; Gilang Adjie Prayudha; Nursapia Harahap (CV. ITTC INDONESIA, 2025)
This study aims to understand the strategies of students at UIN Sumatera Utara (UINSU) in responding to the spread of hoax news on TikTok social media. A qualitative approach with a phenomenological design was used in this study. Data were collected through in-depth interviews with 10 UINSU students. The results showed that UINSU students have shown a high awareness of the dangers of hoaxes on TikTok. They have developed diverse and effective strategies in responding to the spread of hoax news, such as verifying information, comparing information from various sources, and refraining from spreading information that is not yet clear. UINSU students also show a critical and proactive attitude in dealing with hoaxes, such as tracing news sources, identifying uploaders, reading netizen comments, and reporting hoax content to the TikTok platform.